상사의 임파워링 리더십이 조직 구성원의 정서적 몰입에 미치는 영향: 팔로워십의 매개효과 및 조절효과를 중심으로 - 안현서(Hyun-seo An); 윤동열(Dong-Yeol Yoon); 홍권표(Kwon-Pyo Hong) (대한경영학회지, 2020)
급격한 변화에 적극적으로 대응하고자 기업들은 끊임없이 혁신과 변화를 주도하고 있다. 특히 고도의 기술발전과 함께 기업 내 경쟁력의 원천으로 인적자원의 중요성이 더욱 높아지고 있다. 인적자원은 크게 리더와팔로워로 나눠지는데, 과거에는 리더에 초점을 맞추었다면, 최근에는 실제로 행동하는 팔로워에 대한 관심이높아지고 있다. 하지만 공공기관을 대상으로 한 리더와 팔로워에 대한 연구는 부족한 실정이다. 따라서 본연구는 공공기관을 대상으로 팔로워와의 상호작용이 중요시 되는 리더십 중 하나인 임파워링 리더십이 팔로워의 정서적 몰입에 미치는 영향과 그 관계에서 팔로워십의 매개 및 조절효과를 동시에 연구하였다. 이를 위해A공공기관 구성원을 대상으로 설문자료를 배포하여 이 중 회수된 255부의 자료에 대하여 SPSS를 이용한통계분석을 실시하였다. 분석 결과, 임파워링 리더십과 팔로워십은 조직 구성원들의 정서적 몰입에 정(+)적인영향을 주고 있는 것으로 나타났다. 또한 임파워링 리더십과 정서적 몰입의 관계에서 팔로워십의 매개효과는존재하지 않으며, 부(-)의 조절효과를 갖는다고 분석되었는데, 이는 권한 위임을 이용한 임파워링 리더십이리더 행동을 받아들이는 팔로워가 이를 어떻게 받아들이는지에 따라 부정적 영향을 줄 수도 있음을 보여준다.따라서 임파워링 리더십이 긍정적으로 발휘되기 위해서는 팔로워들과의 상호작용에 주의를 더 기울여야 할필요가 있음을 시사한다. Companies are driving change and innovation constantly to respond to dramatic changeof business environment. The importance of human resources as a key source of competitivenessis strengthened with the development of high level of technology. The human resources can be dividedinto leader and follower.The leader was the main object of study in the past, but recently interest in follower has increasedas the main body of action. In addition to the lack of study about leadership and followership in publicinstitutions, this study research on the effect of empowering leadership on affective commitment and bothof the moderating and mediating effect of followership in their relationship at the same time. answers of employees working for the A public agency. The results of the survey showed as follows:Superior’s empowering leadership have a statistically significant influence on affectivecommitment and followership. Followership, like the empowering leadership, has a influence onaffective commitment likewise.In the relationship between empowering leadership and affective commitment, Even thoughthere is no mediating effect, this study show the negative moderating effect of followership.From the results, this study suggest that empowering leadership with the delegation ofauthority can lead to the negative effect depending on how follower accept the superior’s empoweringleadership behaviors.These results suggest that it is really important to focus on interaction with follower fordrawing positive effect of empowering leadership. KCI Citation Count: 0